Towards equitable and inclusive climate adaptation policies and practices - Kawarazuka, Nozomi (International Potato Center, 2022)
The presentation discussed the importance of looking at issues through a lens of gender and social diversities and thus paying attention to differences, inequality, and power dynamics among farmers. It emphasized that women-oriented technologies and adaptation strategies can help strengthen resilience to climate change at the community level.